Effect of dialysis dependence and duration on post-coronary artery bypass grafting outcomes in patients with chronic kidney disease: A nationwide cohort study in Asia. (15th November 2016) - Chen, Shao-Wei; Chang, Chih-Hsiang; Lin, Yu-Sheng; Wu, Victor Chien-Chia; Chen, Dong-Yi; Tsai, Feng-Chun; Hung, Ming- Jui; Chu, Pao-Hsien; Lin, Pyng-Jing; Chen, Tien-Hsing
Abstract: Background: Chronic kidney disease (CKD) is associated with adverse outcomes in patients who undergo coronary artery bypass grafting (CABG). However, the impact of preoperative dialysis dependence and duration in CKD patients on outcomes after CABG has limited research. Objectives: To evaluate the effect of preoperative dialysis dependence and duration on CABG outcomes in patients with CKD. Methods: A total of 33, 920 patients without CKD and 2573 patients with CKD, all of whom underwent isolated CABG between 1998 and 2009, were identified using the Taiwan National Health Insurance Research Database. The patients with CKD were divided into non-dialysis ( N = 1167), dialysis < 3 years ( N = 749), and dialysis ≥ 3 years ( N = 657) groups. The primary outcomes were cumulative incidence of all-cause mortality, cardiovascular (CV) death, and myocardial infarction (MI) or repeat revascularization. Results: After adjustment of all covariates, a higher all-cause mortality was associated with dialysis ≥ 3 years than with dialysis < 3 years (hazard ratio [HR], 1.56; 95% confidence interval [CI], 1.35–1.80; P < 0.001) and with non-dialysis (HR, 1.41; 95% CI, 1.20–1.66; P < 0.001) after 2 years of follow-up. Similar results were observed for CV death. In addition, both the dialysis groups had a higher risk of MI or revascularization than the non-dialysis group. Furthermore, subgroup analysis revealed that longer duration was associated with a higher risk of 30-day mortality ( P for linear trend < 0.001). Conclusions: Among the CABG recipients, dialysis dependence is associated with a higher incidence of MI or repeat revascularization, and longer dialysis duration is associated with a higher risk of mortality. Highlights: First assessment of impact of dialysis dependence and duration on CABG outcomes Longer dialysis duration is associated with a higher risk of mortality. Dialysis dependence is associated with a higher MI or repeat revascularization.